The Influence of GRDP, Mean Years of Schooling and Life Expectancy on the Human Development Index Across Regencies and Municipalities of Bali Province - Ayu Mutia Zahwa; Ruth Eviana Hutabarat (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP) at constant prices, Mean Years of Schooling (MYS), and Life Expectancy at Birth (LEB) on the Human Development Index (HDI) in regencies/cities of Bali Province during the 2015–2024 period. This study is motivated by Bali's position as the province with the fifth-highest human development index nationally, supported by the tourism sector, yet it has not achieved the highest human development category at the provincial aggregate level. This research employs a quantitative approach using panel data regression methods. Secondary data were obtained from the Central Bureau of Statistics (BPS), with the Fixed Effect Model (FEM) selected as the most appropriate model through specification tests. The research findings indicate that Mean Years of Schooling and Life Expectancy have positive and significant effects on HDI. Conversely, GRDP does not significantly influence HDI. The simultaneous test demonstrates that all three independent variables collectively have a significant effect on HDI. The Adjusted R-square value of 0.988 indicates that the model explains 98.8% of HDI variation in Bali during the study period. These findings emphasize the importance of strengthening the education and health sectors as key strategies for enhancing human development, as well as the need for more effective economic equalization policies to ensure that economic growth delivers more inclusive impacts.